Preparation, characterization and thermal properties of dodecanol/cement as novel form-stable composite phase change material - Memon, S.; Lo, T.; Cui, H.; Barbhuiya, Salim (ELSEVIER, 2013)
This research was aimed at preparing novel form-stable composite phase change material (PCM) for thermal heat storage application in buildings. Dodecanol was incorporated into cement through vacuum impregnation technique. The microstructure, chemical compatibility, thermal properties, thermal stability and reliability were determined by environmental scanning electron microscope (ESEM), Fourier transformation infrared spectrum analysis (FTIR), differential scanning calorimetry (DSC), thermal gravimetric analyzer (TGA) and thermal cycling test. Test results showed that the maximum mass fraction of dodecanol retained in cement without seepage was 9%. This composite was characterized as form-stable composite. FTIR results indicated that the form-stable composite is chemically stable. The melting temperature and latent heat of the form-stable composite were found to be 21.06°C and 18.39 J/g. TGA and thermal cycling test results revealed that the form-stable composite is thermally stable and reliable. It can therefore be concluded that the prepared form-stable composite is a potential candidate for thermal energy storage application in buildings. With the help of an example it is shown that the 2 storey residential building has the capacity to store 2448 MJ of thermal energy. This, in turn, will have significant impact in reducing the energy consumption of buildings.